(untitled) (Comprehensive Journal of Science, 2026)
AbstractThe study aimed to investigate the impact of artificial intelligence applications on the effectiveness of electronic accounting systems in commercial banks in the city of Tripoli. The study adopted artificial intelligence applications as the independent variable and the effectiveness of electronic accounting systems in banks as the dependent variable. A simple random sample of 122 individuals was selected, with 119 questionnaires analyzed using the SPSS software, resulting in a loss of 3 questionnaires. The descriptive analytical approach was employed to interpret the relationship between the variables. The study concluded that the accounting system in the bank reduces human errors in recording and processing banking transactions and achieves a noticeable saving in operational costs. The study recommended unifying expert systems in compliance processes and routine decisions to reduce errors, while emphasizing transparency to meet legal requirements.